2020
DOI: 10.1302/0301-620x.102b3.bjj-2019-1203.r1
|View full text |Cite
|
Sign up to set email alerts
|

Hip displacement and dislocation in a total population of children with cerebral palsy in Scotland

Abstract: Aims The purpose of this study was to compare the prevalence of hip displacement and dislocation in a total population of children with cerebral palsy (CP) in Scotland before and after the initiation of a hip surveillance programme. Patients A total of 2,155 children with CP are registered in the Cerebral Palsy Integrated Pathway Scotland (CPIPS) surveillance programme, which began in 2013. Physical examination and hip radiological data are collected according to nationally agreed protocols. Methods Age, Gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 7 publications
1
37
2
3
Order By: Relevance
“…In comparison with the Scottish "pre-surveillance" and Scottish surveillance CPIPS cohorts 16 (Table 4), the mean age of the children in Scotland was 1.5 years lower at follow-up than that of the Finnish children (n = 253; p < 0.001). The proportion of children with hip displacement in Finland (8.3%) was lower than in the Scottish "pre-surveillance" cohort (10%, p = 0.41), but higher than in the Scottish CPIPS cohort (4.5%, p = 0.009).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In comparison with the Scottish "pre-surveillance" and Scottish surveillance CPIPS cohorts 16 (Table 4), the mean age of the children in Scotland was 1.5 years lower at follow-up than that of the Finnish children (n = 253; p < 0.001). The proportion of children with hip displacement in Finland (8.3%) was lower than in the Scottish "pre-surveillance" cohort (10%, p = 0.41), but higher than in the Scottish CPIPS cohort (4.5%, p = 0.009).…”
Section: Resultsmentioning
confidence: 94%
“…This was done by analyzing those members of this study cohort who met the inclusion criteria in two previously published studies. 15,16 The 2011 study by Elkamil et al 15 compared a Norwegian cohort of children with CP not enrolled in a surveillance program to the children in a comparable Swedish cohort in the CPUP. This study included children 7-15 years of age in GMFCS levels III-V. Data on hip displacements/dislocation, hip surgeries, and radiographic examinations were collected from medical records in Norway and from the CPUP register in Sweden.…”
Section: Design Study Population and Proceduresmentioning
confidence: 99%
“…2,3 The dyskinetic types are mostly caused by lesions in the bilateral deep grey matter, such as the thalamus and putamen (TP) and globus pallidus (GP). 4,5 The prevalence of hip dislocation was reported to be 15-35% in patients with CP of all types [6][7][8][9] and 10-48% in those with dyskinetic cerebral palsy (DCP). 10,11 Hip displacement or dislocation often results in the destruction of the hip joint cartilage, causing pain in the hip and limitations in range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 2,4,25,31,38 have so far identified only SP and high levels of GMFCS as factors associated with NHD.…”
Section: Discussionmentioning
confidence: 99%